Management of High Secondary Education After Regional Government Law - Andi Akbar Herman; Muhammad Jihadul Hayat (Journal of Human Rights, Culture and Legal System, 2021)
Education is the constitutional right of every citizen, as mandated in the 1945 Constitution of the Republic of Indonesia, so that that good education management will support the progress of a nation. The tug of war on government affairs in education carried out by the central government to local governments from districts to provinces has further distanced public services. The type of research used in compiling this research is empirical legal research. The results showed that education management had implications for the ineffective management of senior secondary education in the North Kolaka district, from budget management, management of facilities and infrastructure, and management of human resources, no longer running effectively. This situation forced the provincial government to establish a branch office in the North Kolaka district to support administrative arrangements in the North Kolaka district.Keywords: Education; Transfer of Authority; Regency and Province.